The concept of the schizophrenic lifeworld revisited - Kramer, Marco; Mavrogiorgou, Paraskevi; Juckel, Georg (Frontiers in Psychiatry, 2025)
Disturbances regarding the lifeworlds of patients with mental disorders are recurrently mentioned in psychiatric literature, but the concept often remains poorly defined and unclear. The present article takes the lifeworld in schizophrenia as an example to elucidate this concept. First, the concept “lifeworld” is traced back to its philosophical roots. The classical phenomenology particularly of Edmund Husserl is revisited to establish its general meaning. Secondly, synthesizing classical and current phenomenological-psychopathological literature with empirical findings, we explore different interpretations regarding schizophrenia and their relation to existing theories: (1) a general loss of lifeworld through diminished natural self-evidence, (2) the constitution of an idiosyncratic private world (Eigenwelt), (3) the perception of a strange and alien world (Fremdwelt), and (4) schizophrenia as part of our shared intersubjective lifeworld, albeit with a particular vulnerability to social passivity and exclusion. We argue for a pluralistic understanding that situates schizophrenic lifeworlds on a spectrum between isolation and participation, between radically anomalous experiences and shared lifeworlds. Therapeutically, the analysis highlights the importance of establishing bridges of shared self-evidence, attentive presence, and supportive milieus, while acknowledging the protective and emancipatory functions of private worlds. More broadly, acknowledging schizophrenic lifeworlds as embedded in, yet challenging, our shared world opens new directions for research and calls for a more inclusive psychiatry.